2016
DOI: 10.1177/2050312116670405
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder patients’ perceptions of healthcare delivery platforms

Abstract: Objectives:To assess the acceptability and quality of web-based videoconferencing telemedicine consultation platform in the treatment of opioid use disorder at TrueNorth Medical Centre.Methods:We conducted an interview based quality improvement initiative using an investigator-designed questionnaire. The questionnaire consisted of 17 Agree/Disagree questions, measured on a 7-point Likert scale and 2 questions where patients had the ability to elaborate qualitatively on their perceptions and experiences with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It is possible telehealth was more convenient for patients and helped reduce stigma that has been associated with receiving care within SUD or mental health specialty clinics. 14 Several facilities had been offering some visits through a video conference calls for M-OUD maintenance before COVID-19 and found it easy to continue care for patients with OUD using this technology. During COVID-19, several facilities expanded to offer telehealth for M-OUD initiation (also called induction) on buprenorphine.…”
Section: Commentarymentioning
confidence: 99%
“…It is possible telehealth was more convenient for patients and helped reduce stigma that has been associated with receiving care within SUD or mental health specialty clinics. 14 Several facilities had been offering some visits through a video conference calls for M-OUD maintenance before COVID-19 and found it easy to continue care for patients with OUD using this technology. During COVID-19, several facilities expanded to offer telehealth for M-OUD initiation (also called induction) on buprenorphine.…”
Section: Commentarymentioning
confidence: 99%
“…Telemedicine has become a common method for delivering medical services in urban and rural areas (Liddy, Rowan, Afkham, Maranger, & Keely, 2013), demonstrating significant clinical benefit as well as time and cost savings for patients (Dullet et al, 2017). Patients with OUD report that the delivery of MAT via telemedicine is an acceptable modality of treatment (Rakita, Giacobbe, & Cavacuiti, 2016), and patients receiving MAT via telemedicine have similar rates of abstinence and retention at treatment at 90 days and 1 year, compared to those receiving MAT inperson (Zheng et al, 2017). In one large study conducted in Canada, patients receiving MAT via telemedicine had higher treatment retention rates at one year, compared to those receiving in-person care, 50% vs. 39% respectively (Eibl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, length of opioid use, drug of choice, length of current treatment, prior number of OUD treatment attempts, and past OUD treatment methods were also assessed. Qualitative Interview Guide Questions for the semistructured interview guide were developed based on previous studies of patient experience with buprenorphine (da Silveira et al, 2018;Ostrach & Leiner, 2019;Rakita et al, 2016), predictors of buprenorphine treatment retention (Dayal & Balhara, 2017), and the primary investigator's 3 years of experience as a buprenorphine provider. Questions were used as a guide and followed up with probing questions to further our understanding of participants' experiences of OUD care in this NP-facilitated telehealth program.…”
Section: Methodsmentioning
confidence: 99%
“…Findings suggested videoconferencing was acceptable for delivering the intervention. In another study, Rakita et al (2016) examined the acceptability and preference of face-to-face treatment versus telemedicine among 30 patients receiving OUD treatment. Participants completed questionnaires and interviews and found that most ( n = 14, 47%) preferred face-to-face over telemedicine consultations, six (20%) preferred telemedicine, and 10 (33%) indicated no preference.…”
mentioning
confidence: 99%